Determination of the Maximum CO2 Sequestration Capacity of Slovenian Waste Ashes Using Thermogravimetry and Calcimetry - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
There are several ways to utilize as-received or pre-treated waste ash, one of the most promising is by accelerated mineral carbonation. Ashes with a high content of Ca and Mg compounds, such as ashes from wood biomass, are ideal candidates for sequestration. Due to the shift toward renewable fuels, ash from biomass as a by-product of solid fuel combustion is therefore available in huge quantities. As part of the EU AshCycle project, we have analyzed ashes from different incineration and thermal power plants to determine their carbon sequestration potential. These include various waste ashes from Slovenia, which were subjected to accelerated carbonation in a closed carbonation chamber with a CO2 concentration of 4% (v/v), 80% relative humidity and a temperature of 40 °C until maximum CO2 uptake was reached. CO2 quantification was performed using calcimetry (pressure calcimeter) and thermogravimetry. We have shown that ash from wood biomass and the co-combustion of wood waste and paper sludge have a high CO2 sequestration potential in comparison to others. The direct use of wood biomass ash for CO2 sequestration in carbonated building products could significantly benefit the circular economy, especially since 70% of wood biomass ash is still landfilled.